An Occult of Irrelevance? Multimethod Research and Engagement with the Policy World. (2nd January 2016) - Fazal, Tanisha M.
Abstract : Many security studies scholars concerned with the policy relevance of the field have argued that the use of quantitative methods impairs policy relevance. I investigate this claim by looking at the relationship between research methods on the one hand and the supply of and demand for policy-relevant research on the other. I argue that scholars using quantitative methods, either on their own or in tandem with qualitative methods, appear to be increasingly likely to conduct and disseminate policy-relevant research. I also find that curricular changes in policy schools as well as new information technologies mean that policymakers are increasingly able to consume research based on quantitative methods. These trends suggest that the current focus on methodology as the explanation for policy irrelevance may be misplaced.